Molecular characterization and comparative genomic analysis of Acinetobacter baumannii isolated from the community and the hospital: an epidemiological study in Segamat, Malaysia. Issue 4 (5th April 2023) - Muzahid, Nazmul Hasan; Hussain, Md Hamed; Huët, Marie Andrea Laetitia; Dwiyanto, Jacky; Su, Tin Tin; Reidpath, Daniel; Mustapha, Faizah; Ayub, Qasim; Tan, Hock Siew; Rahman, Sadequr
Abstract : Acinetobacter baumannii is a common cause of multidrug-resistant (MDR) nosocomial infections around the world. However, little is known about the persistence and dynamics of A. baumannii in a healthy community. This study investigated the role of the community as a prospective reservoir for A. baumannii and explored possible links between hospital and community isolates. A total of 12 independent A. baumannii strains were isolated from human faecal samples from the community in Segamat, Malaysia, in 2018 and 2019. Another 15 were obtained in 2020 from patients at the co-located tertiary public hospital. The antimicrobial resistance profile and biofilm formation ability were analysed, and the relatedness of community and hospital isolates was determined using whole-genome sequencing (WGS). Antibiotic profile analysis revealed that 12 out of 15 hospital isolates were MDR, but none of the community isolates were MDR. However, phylogenetic analysis based on single-nucleotide polymorphisms (SNPs) and a pangenome analysis of core genes showed clustering between four community and two hospital strains. Such clustering of strains from two different settings based on their genomes suggests that these strains could persist in both. WGS revealed 41 potential resistance genes on average in the hospital strains, but fewer ( n =32) were detected in the community strains. In contrast, 68 virulence genes were commonly seen in strains from both sources. This study highlights the possible transmission threat to public health posed by virulent A. baumannii present in the gut of asymptomatic individuals in the community.